2009
DOI: 10.1111/j.1540-8175.2008.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Strain Rate Imaging in Cardiomyopathy

Abstract: The most common indication for an echocardiogram is for the assessment of left ventricular (LV) function and, in the evaluation of cardiomyopathy (CM), this becomes even more important. However, conventional echocardiographic measures of ventricular function are insensitive at detecting subtle perturbations in contractility. In patients with CM, the ability to detect abnormalities early in the course of the disease to establish a diagnosis can be critical and often may influence specific treatments administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Therefore, the tissue Doppler imaging is mainly used to detect one-dimensional myocardial motion and strain in the long axis parallel to ultrasound beam [14]. Unlike Doppler derived strain, Two-dimensional speckle tracking (2D-STE) is angle independent, which measures the strain by tracking speckles, which are acoustic backscatter generated by ultrasound interactions with the myocardium [15]. However, 2D-STE has limitations for its 2D imaging-based method.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tissue Doppler imaging is mainly used to detect one-dimensional myocardial motion and strain in the long axis parallel to ultrasound beam [14]. Unlike Doppler derived strain, Two-dimensional speckle tracking (2D-STE) is angle independent, which measures the strain by tracking speckles, which are acoustic backscatter generated by ultrasound interactions with the myocardium [15]. However, 2D-STE has limitations for its 2D imaging-based method.…”
Section: Discussionmentioning
confidence: 99%
“…strain and strain rate. 2,6,7 Various studies have shown its greater sensitivity in detecting myocardial dysfunction early 2,6-11 and its possible usefulness in stratifying prognosis of CHF patients. 12,13 The aim of the study was to evaluate the independent role of 2D speckle tracking LV longitudinal strain in predicting cardiovascular death, heart transplantation, hospitalization due to acute decompensated heart failure (ADHF) and the occurrence of ventricular arrhythmic events in a large series of outpatients with CHF.…”
mentioning
confidence: 99%
“…Therefore only active or intrinsic motions of the myocardium are considered. In humans as well as in various animal models of myocardial ischemia, these indices (especially peak systolic strain and strain rate) often prove to be more discriminating than classical TDI parameters for the appreciation of myocardial viability after an ischemic accident, the assessment of myocardial function, or walls synchronism [18,[50][51][52][53][54].…”
Section: Strain Rate = Strain/δτmentioning
confidence: 98%
“…These parameters represent the basis for techniques of strain imaging and strain rate imaging, respectively [27,[48][49][50][51][52][53][54]. …”
Section: Strain Imaging and Strain Rate Imagingmentioning
confidence: 99%